Menumbuhkan Jiwa Kepemimpinan melalui Pembelajaran Soft Skill Leadership di Kota Samarinda - Dzulfa Alya; Aidah Nafisah Anwar; Indri Kristiani Matangkin; Joana Oktavia Sapan; Arwin Sanjaya; M. Tommy Fimi Putera (Keyboard Jurnal Pengabdian Masyarakat, 2025)
Leadership is the ability or intellegence of a person to encourage a group of people to work together in carrying out activities aimed at achieving common goals. The webinar with the theme "Unlock Your Leadership Potential" was held to provide insight and practical strategies in developing leadership skills through this learning. The implementation method adapts the Laswell and Shannon Weavers's model with stages ranging from preparation, implementation and provision of materials or education, to the evaluation and feedback stages. The participants' understanding of leadership through this soft skill learning was generally quite good, as evidenced by the participants' positive responses to the material presented and active participation in the question and answer and discussion sessions. This indicates that the webinar succeeded in achieving its main objective of providing insight and practical strategies in developing leadership skills. In addition, the evaluation from participants and the suggestions given also provided valuable input for organizing similar activities in the future, including in terms of compiling materials, delivering, and organizing sessions. With this webinar, it is hoped that participants can understand the importance of non-technical skills in leadership, recognize various important knowledge for a leader, and obtain methods and techniques to improve these skills.